Public Universities, Tuition and Competition: A Tiebout Model - Robert Schwager (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
A simple Tiebout model is presented where states provide university education to both immobile and mobile students. State governments choose the quality of public universities by trading off the value of education for the local immobile student population and the costs, net of tuition revenues, of running the university. The quality of education and the assignment of students to universities in an efficient allocation are characterised. It is shown that decentralised decisions result in efficient choices if states are allowed to choose tuition levels freely. If tuition is capped, ine?ciently low qualities are likely to arise.
Keywords: H75; H77; I28; 330; higher education; migration; fiscal externality; club good; tuition; Hochschule; Studienfinanzierung; Teilstaat; Studierende; Institutioneller Wettbewerb; Klubtheorie; Theorie